Pengaruh Trait Kepribadian Big Five dan Konformitas Teman Sebaya Terhadap Agresivitas Anak Punk di Jabodetabek - Syifa Fauziah; Diana Mutiah (Raheema, 2015)
This research is performed to understand the effect of personality traits ‘big five’ and the peer conformity towards the punk youngster aggressive acts in Jabodetabek. The sample of this research is 181 persons of the punk youngster. The sampling technique used is nonprobability sampling. Meanwhile, the data analysis applied on thi research is Multiple Regression Analysis at 0,05 significance level. The research wraps up that there is a substantial effect between the ‘big five’ personality traits and the peer conformity towards the assertive behaviors of the punk youngste in Jabodetabek. The proportion variable of coping explained by all of the independent variables is 38.3%, while the remaining 61.7% is affected by other variables out of this research. Moreover, the result of minor hypothesis shows the  conscientiousness and neuroticism, compliance, and conversion have an important impact to the children’s offensive acts in Jabodetabek. Otherwise, the ‘big five’ personality traits, , agreeableness, extraversion, and openness do not affect significantly to the aggressive behaviors of the Punk youngsters in Jabodetabek.